Nitrogenase Activity and IAA Production of Indigenous Diazotroph and Its Effect on Rice Seedling Growth - Purwanto Purwanto; Yuyun Yuwariah; Sumadi Sumadi; Tualar Simarmata (AGRIVITA, Journal of Agricultural Science, 2017)
The diazotroph bacteria as ecofriendly biofer-tilizers play an important role in improving the N status and availability of paddy soil. Laboratory experiment to study nitrogenase activity and IAA production of diazotroph from rice rhizosphere and to assess its effect on the growth of rice seedling has been conducted from September to October 2014 in Agronomy and Horticulture Laboratory Faculty of Agriculture Jenderal Soedirman University, Purwokerto. The experiment was arranged as a completely randomized design and consisted of seven treatments and provided with 4 replications. The treatments were the isolates of indegenous diazotroph (T1 = A11003, T2 = A230041, T3 = A24001, T4 = A230022, T5 = A230021, T6 = A230042 and T7 = without inoculation). The nitrogenase activity measured by acetylene reduction assay method and IAA production was measured by HPLC method. Plant height, leaf greeness, leaf area, total dry weight and total root length were determined on 21 days after sowing. The experimental results showed that the isolat A230021 was identified as Rhizobium sp. LM-5 and have the highest nitrogenase activity at 0.07 µM C2H4 ml-1 h-1 and IAA production reached 19.01 ppm. Inoculation with strains of diazotroph enhanced chlorophyl content, total root length, and biomass production.